2021
DOI: 10.3389/fsurg.2021.711685
|View full text |Cite
|
Sign up to set email alerts
|

Electrocautery vs. Stapler in Comparing Safety for Segmentectomy of Lung Cancer: A Meta-Analysis

Abstract: Background: Electrocautery and staplers are regarded as the two most common surgical instruments for dissecting the intersegmental plane in segmentectomy. We performed a meta-analysis to compare electrocautery and staplers in terms of their safety and effects.Methods: A systematic search strategy was performed using PubMed, and the retrieval time was up to April 1, 2020. Odds ratio (OR) and mean differences (MDs) with 95% CI were applied to determine the effectiveness of dichotomous or continuous variables, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 6 However, the use of surgical staplers, electrocautery, or other energy devices for dissection of the intersegmental plane remains controversial. 15 , 16 , 17 , 18 , 19 In a previous prospective study, the degree of pulmonary function preservation did not change in a comparison of intersegmental dissection using surgical staplers or electrocautery, and the surgical stapler group required more staple cartridges. However, the medical costs remained the same because of increased complications in the electrocautery group.…”
Section: Discussionmentioning
confidence: 85%
“… 6 However, the use of surgical staplers, electrocautery, or other energy devices for dissection of the intersegmental plane remains controversial. 15 , 16 , 17 , 18 , 19 In a previous prospective study, the degree of pulmonary function preservation did not change in a comparison of intersegmental dissection using surgical staplers or electrocautery, and the surgical stapler group required more staple cartridges. However, the medical costs remained the same because of increased complications in the electrocautery group.…”
Section: Discussionmentioning
confidence: 85%
“…An SLR comparing electrocautery versus stapler in segmentectomy reported that electrocautery resulted in a greater incidence rate of air leaks. 20 Experts agreed that compared with staplers, the use of energy devices alone (eg, electrocautery, ultrasonic scalpel) may result in a greater rate of postoperative air leaks. Energy devices may result in some heat damage to lung tissues, which may give rise to postoperative complications such as air leaks.…”
Section: Discussionmentioning
confidence: 99%
“…Energy devices may result in some heat damage to lung tissues, which may give rise to postoperative complications such as air leaks. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The uniform, solid coagulation layer caused by sealing may also be unfavorable for recognization of the ISD. Compared with stapling, the inferiority of energy devices mainly include more complex procedures, increased risk of air leakage; 22–25 and dependence on clear and persistent ISD. Therefore, an appropriate combination is believed to be better than alone 9,11 …”
Section: Discussionmentioning
confidence: 99%